Large traumatic vulvar hematoma managed with a simple incision: A case report. (July 2021) - Tjokroprawiro, Brahmana Askandar
Abstract: Introduction and importance: Non-obstetric vulvar hematoma is a rare condition. With only few cases reported, no standard consensus exists on the best management of vulvar hematomas. Herein, we report the successful management of a large trauma-induced vulvar hematoma through a simple incision under local anesthesia. Localized large vulvar hematomas can be treated with this simple procedure. Case presentation: A 38-year-old woman presented with vulvar pain following a fall. Investigations revealed a large painful hematoma in the right labium majus. Imaging revealed that the hematoma was localized and the pelvic structure was normal. We successfully treated the hematoma by making an incision in the right labium majus under local anesthesia to evacuate the clot and ligate the bleeding points. She was discharged in a good condition after two days. Discussion: Non-obstetrics vulvar hematoma is rare particularly the large hematoma. A blunt trauma may cause a large vulvar hematoma. There is no standard management of vulvar hematomas since the incidence is very low. The important step in managing vulvar hematoma is detecting the localization of the hematoma and evaluating other pelvic structures. Most of vulvar hematoma is isolated in the soft tissue around the labium majus and the vagina without further extension. After confirming that the large vulvar hematoma is localized and there are no injuries to the other pelvic structures, a simple incision and bleeding points ligation under local anesthesia can be performed to relieve the pain and prevent pressure necrosis. Conclusion: Simple incision under local anesthesia is effective for managing large vulvar hematomas and reduces the recovery time. Highlights: Blunt trauma may cause a large vulvar hematoma Large vulvar hematoma is commonly localized and should be confirmed by imaging Incision for large localized vulvar hematoma will relieve the pain quickly and may prevent necrosis